Testing ChatGPT in International Relations Classrooms: Potentialities, Limitations, and What’s Next - Rivetti, Paola; Banerjee, Rituparna; O’Mullane, David (PS, political science & politics, 2025)
Whereas significant attention has been devoted to online/blended teaching and related tools, open GenAI chatbots and large language models and writing programs have received comparatively less attention as instruments that impact our teaching and assessment methods. The pedagogies of political science and international relations somehow trail behind in understanding and addressing them. For those who are teaching these subjects, it is of great importance to come to terms with AI and its impact on how we should assess students. This article describes an eight-week laboratory during which we experimented with and discussed ChatGPT’s utilizations with our students. The goal of the laboratory was to revise which type of learning objectives our teaching should have and which type of assessment methods are best suited for an environment in which GenAI is present and used regularly. Should we ban it or should we instead focus on teaching students how to use it responsibly and ethically, as well as developing a shared understanding of what GenAI is good for (if anything at all)? Consequently, which learning objectives and assessment methods should we adopt?